PEMBELAJARAN DARING MUATAN PEMBELAJARAN IPS PADA KELAS V SD - Tea Kirana, Kesya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This study aims to know the implementation of online learning process in social studies for fifth grade elementary school students at SDN Pondok Kelapa 06 Pagi Jakarta, as well as to know the role of learning components in online learning of social studies subject. The subjects in this study were teachers and students of class V B SDN Pondok Kelapa 06 Pagi Jakarta in 2021/2022 academic year. This research is a qualitative with descriptive method. The data collection instruments used are observation, interviews, and documentation. The results showed that the use of What’sApp as a medium in delivering learning makes it easier for teacher. However, the teacher cannot monitor the activities carried out while students are studying and doing exercises, so teacher cannot ensure that students understand the material of social studies subject optimally.